PREVALENCE AND ANTIBIOTIC RESISTANCE PROFILES OF BACTERIAL ISOLATED FROM BURN WOUND INFECTIONS - Abdul Salam Abdul Sattar Abdul Azez; luma N.abdulrazaq abdulrazaq; Mohammed Nazhan Radaan Alqaisi; Mohammed Sabah Mohammed; Hadeel Ahmed Kenoosh (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Burn wound infections remain a sizeable assignment, especially because of the superiority of multidrug-resistant gram-negative organisms. The objective of this take a look at was to assess the superiority of bacterial infections in burn wounds, perceive the most not unusual bacterial species, and determine their antibiotic resistance profiles. A overall of eighty samples had been amassed from burn sufferers. Bacterial cultures were performed, and the isolated bacteria were identified using standard microbiological techniques. Antibiotic susceptibility testing was conducted using the disc diffusion method. In this study, 44 samples (73.3%) tested positive for bacterial growth. Pseudomonas sp. was the most commonly isolated bacteria (56%), followed by Staphylococcus aureus (22%) and others. Antibiotic resistance profiling revealed high resistance rates among the isolated bacteria, with Rifampicin showing the highest resistance rate (80%), followed by Cefotaxime (64%) and Amoxicillin (56%). The high prevalence of multidrug-resistant gram-negative organisms in burn wound infections underscores the urgent need for effective antibiotic management strategies. These findings highlight the importance of continuous surveillance of antibiotic resistance patterns and the development of tailored treatment protocols to mitigate the morbidity and mortality associated with burn wound infections. Additionally, there is a critical need for the development of new antimicrobial agents and infection control measures to combat the growing threat of antibiotic resistance in burn care settings.